Contrastive Analysis Of Loanword From Arabic Language In Indonesian Language - Ahmad Arifin (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2019)
Contrastive analysis is a linguistic study that aims to describe the equations and differences between two languages and the distinctiveness of each language. The Arabic language is a language that has distinctiveness, privileges, and uniqueness from alphabets, words, sentences, structure, and uslubcompared to other languages. It is also the oldest language in the world. Therefore, the development of the Indonesian language now is inseparable from the contribution of Arabic language, like in religion, culture, science, politics, social, culture, etc. For example, we can find the words “musyawarah, masjid, majlis, jihad, kitab, sholat, zakat, umat, umum, markas, amal, doa, ilmu, halaqah, hikayat, kalbu, tariqat, kalam, majalah, and others. All of them has added and enriched the treasury of vocabulary in the Indonesian language and made it easy for Indonesian Muslims to worship. Using the Arabic word to the Indonesian language based on contrastive analysis can be existence full adaptation pattern, partial adaptation pattern or adjustment pattern of lafadz. It also happened because of eviation/error in the adaptation pattern or a deviation/error in the delivery of meaning.